Integrated Waste Management Strategy Through Waste BANK and Maggot Cultivation in RW 13 Ciwaruga Village, Parongpong District, West Bandung Regency, West Java Province - Sartika, Euis; Karnisah, Iin; Puspitasari, Ira; Rahmah, Ilma Yullinda; Arnoi, Khoirun Nisaa; Fadli, Dicky Muhamad; Widyantoro, Frenki Tres (ETHOS: Jurnal Penelitian dan Pengabdian kepada Masyarakat, 2026)
Poor household waste management can lead to environmental pollution and health issues. To address the issue, a community service program was conducted in RW 13, Ciwaruga Village, through Black Soldier Fly (BSF) maggot cultivation for organic waste processing and the establishment of a waste bank for inorganic waste management. The program was implemented using a participatory approach consisting of baseline assessment, community counseling, hands-on training, mentoring, and monitoring and evaluation. These activities aimed to improve household waste segregation, reduce waste generation, and increase the economic value of waste through integrated organic and inorganic waste management. Baseline assessment results indicated that community knowledge and attitudes toward waste management were relatively high (75% and 60%, respectively), while waste management practices remained below 50%. Following the intervention, knowledge increased from 75% to 92%, attitudes improved from 60% to 85%, and proper waste management practices increased from below 50% to 80%. Community members were also able to independently sort household waste, implement BSF maggot cultivation for organic waste treatment, and manage a community-based waste bank. These findings demonstrate that the program successfully strengthened community capacity for integrated and sustainable household waste management, reduced the volume of waste sent to landfills, and generated environmental and economic benefits.